Quizizz Application in Students Learning Outcomes: Teachers and Students Perception - Daulay, Sholihatul Hamidah; Ramadhan, Achmad; Wahyuni, Sri (Modality Journal: International Journal of Linguistics and Literature, 2023)
AbstractThis study explores the use of the Quizizz application in enhancing student learning outcomes: Perspectives from both teachers and students. The background of this research underscores the significance of student learning outcomes as one of the key aspects of the classroom environment. In order to gauge student learning outcomes, teachers must understand the motivating factors for students, including the learning media employed, to encourage enthusiasm for learning in the classroom and completion of assigned exercises. One of the technological tools that can be employed in this context is the Quizizz application. To assess the effectiveness of Quizizz in the classroom, it is crucial to comprehend the perceptions of both teachers and students regarding its application. This research aims to elucidate the perspectives of teachers and students on the use of the Quizizz application in enhancing student learning outcomes. The research methodology employed is qualitative descriptive. Data were collected from one English language teacher and ten seventh-grade students. Data collection instruments included observation and interviews. The research findings indicate that, according to the perceptions of all participants, the Quizizz application is deemed easy to use, understandable, enjoyable, motivating, engaging, effective, and capable of reducing boredom when studying English. Based on these research findings, it can be concluded that the Quizizz application has the potential to enhance student motivation and learning outcomes. Therefore, it is recommended to integrate Quizizz into the classroom learning process as a means of motivation and improving student learning outcomes.Â Keywords : Perception, Quizizz, Students, TeacherÂ Abstrak Penelitian ini mengeksplorasi Penggunaan Aplikasi Quizizz dalam Meningkatkan Hasil Belajar Siswa: Perspektif Guru dan Murid. Latar belakang penelitian ini merujuk pada pentingnya hasil belajar siswa sebagai salah satu aspek utama dalam proses pembelajaran. Untuk memahami pencapaian belajar siswa, guru perlu memahami faktor-faktor yang memotivasi siswa, termasuk media pembelajaran yang digunakan, agar mereka lebih termotivasi untuk belajar di kelas dan menyelesaikan latihan yang diberikan. Salah satu media teknologi yang dapat digunakan dalam konteks ini adalah aplikasi Quizizz. Untuk menilai efektivitas penggunaan Quizizz di kelas, penting untuk memahami persepsi guru dan siswa terhadap aplikasi tersebut. Penelitian ini bertujuan untuk menjelaskan persepsi guru dan murid terhadap penggunaan aplikasi Quizizz dalam meningkatkan hasil belajar siswa. Metodologi penelitian ini adalah deskriptif kualitatif. Data dikumpulkan dari satu guru bahasa Inggris dan 10 siswa kelas VII. Instrumen pengumpulan data melibatkan observasi dan wawancara. Hasil penelitian menunjukkan bahwa menurut persepsi seluruh partisipan, aplikasi Quizizz dinilai mudah digunakan, mudah dipahami, menyenangkan, mampu memotivasi belajar, menarik, efektif, dan dapat mengurangi kebosanan saat mempelajari bahasa Inggris. Dengan temuan ini, dapat disimpulkan bahwa aplikasi Quizizz memiliki potensi untuk meningkatkan motivasi dan hasil belajar siswa. Oleh karena itu, disarankan untuk mengintegrasikan Quizizz ke dalam proses pembelajaran di kelas sebagai sarana motivasi dan peningkatan hasil belajar siswa.Kata Kunci: persepsi, quizizz, siswa, guru